Smartphone and Self-Harm: A study of TikTok Use as a Risk Factor - Udam, Mikhael; Oktara, Tri Windi; Justitia, Dewi; Putri, Utami Nurhafsari; Karisma, Sally Putri; Fajri, Nurul; Muhazir, Muhazir; Erwinda, Lira (Bulletin of Counseling and Psychotherapy, 2024)
In recent years, the use of social media and the internet has become an inseparable part of everyday life, especially among adolescents. Social media offers a variety of benefits, including ease of communication, access to information, and entertainment. However, concerns have emerged about its negative impact on mental health, especially in relation to self-harm behavior. Adolescents often imitate the trend of self-harm and join in posting the results of scratches on social media. The aim of this study was to determine variations in self-harm in adolescents which are related to the duration of internet use in one day and the use of social media. The research method uses a comparative descriptive approach and Two-Way ANOVA analysis to explore interactions between these variables. Data was collected through an online survey with a self-harm instrument consisting of 18 statements, with respondents choosing from 4 alternative answers available. The results of the analysis show that there are significant differences in self-harm behavior based on the duration of internet use per day and the type of social media used. Adolescents who use the TikTok platform show a higher self-harm score compared to other platforms, especially with longer duration of internet use. These findings indicate that the type and way of using social media has a significant influence on self-harm behavior.